Digital Marketing as an Approach to Achieving Competitive Advantage in Iraqi Football Academies - Hassoun, Hussein Karim; Anoun, Bilal Abbas (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to identify the role of digital marketing as a gateway to achieve competitive advantage in Iraqi football academies on the following questions: What is the reality of digital marketing in Iraqi football academies? What is the reality of competitive advantage in Iraqi football academies? What is the role of digital marketing in achieving competitive advantage in Iraqi football academies? Materials and methods. The research method using the descriptive method was used as the general framework for the study, with surveys as the primary tool for data collection. The research included a pilot sample of (50) individuals consisting of academy owners, coaches, and parents from outside the main sample, in addition to a main sample of (682) individuals, including academy owners, coaches, activity managers, and parents. Result. results of research showed that academies heavily rely on social media platforms to promote their activities and training programs, and that digital marketing plays a significant role in enhancing the academy's image and strengthening its brand. Conclusion. Concluded that the Academy relies on social media to promote its activities and training programs, the Academy uses an official website to present its services and communicate with the public, with a low degree, Football academies in Iraq do not provide advanced training programs that keep pace with world standards, Football academies in Iraq do not rely on qualified and experienced coaches to develop the skills of players.